Mechatronic System For Preserving The Natural Properties Of Cotton Stored In Modules - Kuldashov G.O.; Polvonov A.K. (Stanford Database Library of American Journal of Applied Science and Technology, 2026)
The article analyzes the mechatronic system developed for automated control of microclimate parameters (moisture, temperature, and carbon monoxide gas) during the storage of seed cotton in modules. Using mechatronic principles, the integration of sensors, a controller, and actuators enables the optimization of moisture and temperature regimes. Simulation results in the TRACE MODE environment are presented, along with recommendations for ensuring energy efficiency and maintaining fiber quality stability.